Effect of Innovation and Technology on Productivity and Profitability in Nepalese Commercial Banks - Adhikari, Sarita; Pradhan, Radhe Shyam (Nepalese Journal of Business, 2024)
This study examines the effect of innovation and technology on productivity and profitability of Nepalese commercial banks. Bank productivity and profitability are the dependent variables. The independent variables are mobile banking, e- payment, internet banking, ATM banking, and POS banking. The primary source of data is used to assess the opinions of respondents regarding innovation and technology in Nepalese commercial banks. The study is based on 160 respondents from 25 commercial banks of Nepal. To achieve the purpose of the study, structured questionnaire is prepared. The multiple regression models are estimated to test the relationship and importance of innovation and technology on productivity and profitability in Nepalese commercial banks. The study showed that internet banking has a positive impact on bank productivity and profitability. It indicates that increase in internet banking leads to increase in the bank productivity and profitability. Similarly, ATM service has a positive impact on bank productivity and profitability. It means that better ATM service leads to increase in bank productivity and profitability. The result also shows that mobile banking has a positive impact on bank productivity and profitability. It means that better mobile banking services leads to increase in bank productivity and profitability. Likewise, point of sale has a positive impact on bank productivity and profitability. It indicates that increase in point of sale services in retail stores leads to increase in bank productivity and profitability. Similarly, e-payment technology has a positive impact on bank productivity and profitability. It means that better e-payment technology leads to increase in bank productivity and profitability.